(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As of today, the Indian education system has become one of our most pressing problems. Themost obvious cause for India’s shortfall is its out-of-date educational system.I shall explore issues ofIndian education in this article.Since independence, successive Indian administrations have faced anumber of significant issues in education policy, which has always been an important aspect of thecountry’s development strategy. The following are the major challenges expanding access and quality atall levels of education boosting money, particularly for higher education and raising literacy rates.WhileIndian management and technology colleges are world-class, basic and secondary schools, especially inrural regions, have significant obstacles. While incoming administrations often promise to boosteducation funding and implement structural changes, this has seldom happened in fact.The currentCongress-led administration will be put to the test when it comes to raising educational standards inIndia. It will have to address issues about the curriculum’s substance as well as the underlyingeducational problems.